Effects of the Girls on the Move randomized trial on adiposity and aerobic performance (secondary outcomes) in low‐income adolescent girls. Issue 11 (3rd July 2019) - Pfeiffer, Karin A.; Robbins, Lorraine B.; Ling, Jiying; Sharma, Dhruv B.; Dalimonte‐Merckling, Danielle M.; Voskuil, Vicki R.; Kaciroti, Niko; Resnicow, Kenneth
Summary: Background: Limited, mixed evidence exists regarding the effectiveness of physical activity interventions on adiposity and aerobic performance in adolescent underrepresented populations. Objective: To examine effects of Girls on the Move on body mass index z‐scores (BMI‐z), percent (%) body fat, and aerobic performance in fifth‐ to eighth‐grade underrepresented girls. Methods: A group randomized trial, involving 12 intervention and 12 control schools in low‐income areas, was conducted. Participants (n = 1519) were low‐active girls. The 17‐week intervention included (a) a physical activity club, (b) two motivational interviewing sessions, and (c) one Internet‐based session. BMI‐z was determined from measured height and weight; % body fat was assessed using bioelectric impedance. Aerobic performance was assessed using a shuttle run. Demographics, physical activity (accelerometer), and pubertal development were assessed. Linear mixed models, adjusting for baseline, were used to examine group differences in postintervention. Results: No significant between‐group differences in BMI‐z existed at postintervention, but % body fat increased less among intervention than control group girls (Mchange = 0.43% vs 0.73%). Aerobic performance decreased less in intervention vs control (Mchange = −0.39 vs −0.57). Conclusions: Although the intervention positively impacted % body fat and aerobic performance in underrepresented girls, more research is necessary to determine optimal implementation for yielding greater effects.